Chickenpox infection in children, action to take - H Bruel; D Pinquier (Journal of Vaccines and Immunology - Peertechz Publications, 2020)
What to do in the event of a varicella infection in pregnant women or children is sometimes not well known. Several therapies are available to doctors; specific immunoglobulins, anti virals, vaccination. We propose a decision tree